Formulasi, Uji kualitas Dan Uji Organoleptik Sabun Mandi Padat Menggunakan Bahan Aditif Daun Jambu Biji (Psidium guajava L.) - Sri Handayani; Aris Tiana Anjali (Fakultas Farmasi Universitas Setia Budi, 2020)
Guava leaves have flavonoids, tannins, and alkaloids as main compounds which have been shown to be active as antibacterial and anticarcinogenic agents. However, they have never been used as additives in skin care products because they have a rough texture. The purpose of this research are to formulate the method in the production of bath soap with the leaves as additives, and they were examined in quality and organoleptic tests. Formulation in production of the soap was carried out by means of variations of the method of extracting guava leaves as additives, namely: without additive as a control (A), with water solvent (B), with vegetable oil solvent (C), and powder dried as a scrub (D). The soap quality tests based on SNI 2016 including tests for alkaline or free fatty acid levels, insoluble ingredients in ethanol and unsaponified fat fractions. Organoleptic test was carried out involving 20 panelists. Data were analyzed by ANOVA-Duncan test. It was found that soap quality test for all samples meet INS except free alkali levels in D soap. The hedonic test results show that all soap samples can be accepted by panelists. Based on quality and organoleptic tests, the formulation method for adding guava leaf extract as an additive that produces the best soap is extraction using a water solvent (soap B). For the next study, it is necessary to confirm the biological activity of soap with guava leaf additives because it is very potential to be used as an antimicrobial soap.